2023
DOI: 10.1111/nph.18699
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress induces malformed tomato fruits by breaking the feedback loops of stem cell regulation in floral meristem

Abstract: Summary Fruit malformation is a major constrain in fruit production worldwide resulting in substantial economic losses. The farmers for decades noticed that the chilling temperature before blooming often caused malformed fruits. However, the molecular mechanism underlying this phenomenon is unclear. Here we examined the fruit development in response to cold stress in tomato, and demonstrated that short‐term cold stress increased the callose accumulation in both shoot apical and floral meristems, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…As reviewed by Han et al (2014b), TFs are well characterized examples of such signalling molecules that could play an important part in the determination of fruit size. Recently, it was shown that a cold stress increases callose accumulation in the FM of tomato plants, resulting in impaired feedback loops which regulate the activity of WUSCHEL (WUS) (Wu et al, 2023). The TF WUS specifies the maintenance of stem cell activity in FM, and therefore a deregulation of WUS activity impacts the number of carpel primordia, and ultimately the number of locules inside the fruit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reviewed by Han et al (2014b), TFs are well characterized examples of such signalling molecules that could play an important part in the determination of fruit size. Recently, it was shown that a cold stress increases callose accumulation in the FM of tomato plants, resulting in impaired feedback loops which regulate the activity of WUSCHEL (WUS) (Wu et al, 2023). The TF WUS specifies the maintenance of stem cell activity in FM, and therefore a deregulation of WUS activity impacts the number of carpel primordia, and ultimately the number of locules inside the fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the FW2. feedback loops which regulate the activity of WUSCHEL (WUS) (Wu et al, 2023).…”
Section: How To Reconcile a Function Of Fw22 In Cell-to-cell Communic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports mainly focused on WOX regulation of plant development and growth, but few studies investigated the roles of WOXs in diverse stresses. Tomato SlWUS and Arabidopsis AtWOX6 are involved in cold stress through CBF-independent pathways [ 42 , 59 ]. Rice OsWOX11 and OsWOX13 have been reported to be involved in drought resistance [ 36 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, intercellular communication and molecular exchanges occur through apoplastic and symplastic pathways. Symplastic communication coordinates diverse signals during biological processes, including plant growth, development, and environmental responses (Faulkner, 2018; Gaudioso‐Pedraza et al ., 2018; Azim & Burch‐Smith, 2020; Mellor et al ., 2020; Li et al ., 2022; Wu et al ., 2023). Plasmodesmata provide a direct symplastic channel for cell‐to‐cell molecular transport and play roles in phloem development and root growth (Benitez‐Alfonso, 2014; Yadav et al ., 2014; Sevilem et al ., 2015; Lee & Frank, 2018).…”
Section: Introductionmentioning
confidence: 99%